EFEKTIVITAS PELAKSANAAN PROGRAM BKR DI DESA AIR LESING KECAMATAN MUARA BELITI KABUPATEN MUSI RAWAS - Priatin Priatin; Nasruddin Nasruddin; Syamsah Nas (Jurnal Interprof, 2020)
Based on the motivation aspect of the members, it is not seen that the quality assessment of the quality of the Youth Family Development cadres is positive, while the empowerment aspect of the members is also not maximal in the application of trust and communication to the cadre members of the Youth Family Development from the organizing committee. So it can be concluded that the motivation of members and empowerment of members of Air Lesing Village Youth Families is not effective.